Global longitudinal strain measured by speckle tracking identifies subclinical heart involvement in patients with systemic sclerosis. (29th August 2020) - Guerra, Federico; Stronati, Giulia; Fischietti, Colomba; Ferrarini, Alessia; Zuliani, Lucia; Pomponio, Giovanni; Capucci, Alessandro; Danieli, Maria Giovanna; Gabrielli, Armando
Abstract: Background: Systemic sclerosis is characterised by progressive cutaneous and organ fibrosis. Among all organs, a subclinical heart involvement is difficult to detect through conventional imaging. Design: We evaluated whether speckle tracking-derived global longitudinal strain could help detect early subclinical systolic dysfunction in systemic sclerosis patients without overt clinical involvement. Methods: A case–control, single-centre study on 52 systemic sclerosis patients and 52 age and gender-matched controls. Patients with structural heart disease, heart failure, atrial fibrillation and pulmonary hypertension were excluded. For every patient, standard echocardiographic and speckle tracking-derived variables for the systolic and diastolic function of the left ventricle and right ventricle were acquired. Results: Traditional parameters of left and right systolic function did not differ between systemic sclerosis patients and controls (all P = ns). Left and right ventricular global longitudinal strain was significantly impaired in patients with systemic sclerosis when compared to controls (–19.2% vs. –21.1%; P = 0.009 and –18.2% vs. –22.3%; P = 0.012, respectively). Systemic sclerosis patients had a 2.5-fold increased risk of subclinical left ventricular systolic impairment (odds ratio 2.5, 95% confidence interval 1.1–5.5; P = 0.027) and a 3.3-fold increased risk of subclinical right ventricular systolic impairment when compared to controls (odds ratio 3.3, 95% confidence interval 1.4–7.7; P = 0.004). Alterations in the myocardial deformation pattern of systemic sclerosis patients were homogeneous in the right ventricle and eccentric in the left ventricle. Conclusions: While traditional echocardiographic parameters are ineffective in detecting subclinical systolic impairment, reduced global longitudinal strain is common in patients with systemic sclerosis and significant for both ventricles. Global longitudinal strain could become a low-cost, non-invasive and reliable tool in order to detect early cardiac involvement in systemic sclerosis patients.